Flap choice for closure of open window thoracotomy: a response to the author of the article entitled “the omentum flap for empyema treatment: indications and disadvantages” - Shinohara, Shuichi; Chikaishi, Yasuhiro; Kuwata, Taiji; Takenaka, Masaru; Oka, Soichi; Hirai, Ayako; Imanishi, Naoko; Kuroda, Koji; Tanaka, Fumihiro (Journal of Thoracic Disease; Vol 8, No 12 (December 31, 2016): Journal of Thoracic Disease, 2016)
The principle of empyema treatment includes cleansing the pleural cavity of bacterial infection and removing the empyema cavity. Open window thoracotomy (OWT) is the most invasive and radical treatment for severe empyema; the procedure itself, as well as its closure, is challenging.